If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-21=x+-12
We move all terms to the left:
-21-(x+-12)=0
We add all the numbers together, and all the variables
-(x-12)-21=0
We get rid of parentheses
-x+12-21=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9
| 7x+2x;x=3 | | 3)42=−7(z−3 | | 4x-1.7=2.3 | | z+3z=100 | | 1x-6=-4x-11+5x | | 12j-10=-8j+10 | | X-6=-4x-11+5x | | 3y+5/2y+4=2 | | 38+2=3y+y | | x-17=-54 | | 5÷14=x | | j/200=50 | | 74=5x+4 | | 5c-20/6=100 | | -2+(3y-4)/4=2y-3 | | 5x*4-15x*2=0 | | 40c+20=15c+120 | | 7y-16=12 | | 5x*4-15*2=0 | | 82-y+3y-(126)=0 | | 8x+12=6x+8+14 | | 5i-2=-127 | | 5y-10=100 | | 32=12y | | 108=4x+4 | | b/4-6=(-5) | | 25+z+3z=125 | | 15x-10=15x+14 | | 15x+14=15x-10 | | 82-y+3y=126 | | 4x^2+3x=24–x | | 3/2+t=12 |